Demystify8ing soil health: Policy push for a soil organic carbon mission - Arumugam, Chithra (The Administrator: Journal of LBSNAA)
This article examines the policy imperative of strengthening soil health through a dedicated Soil Organic Carbon (SOC) mission in India. It highlights the critical role of SOC in enhancing agricultural productivity, improving resilience to climate change, and contributing to carbon sequestration. The study explores how policy frameworks can incentivize sustainable farming practices, integrate scientific monitoring, and align with global environmental commitments. By demystifying soil health and situating it within broader debates on sustainability and governance, the paper underscores the need for coordinated action between policymakers, farmers, and civil society to secure ecological balance and food security for the future.
Keywords: Public Policy, Soil Health, Soil Organic Carbon, Agriculture, Sustainability, Climate Change Mitigation, Environmental Policy, India, Carbon Sequestration, Rural Development, Food Security, Policy Innovation